Effects of Resveratrol and Nebivolol on Isolated Vascular and Cardiac Tissues from Young Rats - Candice Pullen; Fiona R. Coulson; Andrew Fenning (Hindawi Limited, 2014)
The mechanisms by which resveratrol and nebivolol induce vasodilation are not clearly understood. It has been postulated that both agents stimulate the production of nitric oxide; however, this remains to be conclusively established. The major aim of this study was to examine the vasodilatory and antiarrhythmic effects of both resveratrol and nebivolol and to provide further insight into possible mechanisms of action. Cardiac and vascular tissues were isolated from healthy male rodents. Results indicate that resveratrol and nebivolol decrease the action potential duration and induce mild vasorelaxation in aortic and mesenteric segments. Relaxation induced by resveratrol was prevented by the addition of verapamil, Nω-nitro-L-arginine-methyl ester, and 4-aminopyridine. This suggests that nebivolol and resveratrol act as putative antiarrhythmic and vasodilatory agents in vitro through possible indirect nitric oxide mechanisms.